Some options for a legal strategy for sustainable development - Nordtveit, Ernst (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
Sustainable development has become a central societal goal for the national and global community and, therefore, also an inherent value that the legal system needs to enhance. The author argues that the current primary strategy to achieve sustainability, based on command-and-control regulation, is insufficient. More fundamental institutional change and ‘smart regulation’ are needed to create adequate incentive structures and facilitate sustainable practices. The strategy should create incentives and opportunities for individuals and corporations to choose sustainable alternatives. Environmental degradation is primarily a result of discrepancies in private and public costs. Traditional command-and-control regulations, in which the state prescribes standards for action or uses taxation to level out discrepancies in private and social costs, are insufficient to solve the global community’s large and complex issues in dealing with poverty, pollution, natural resource depletion, biological degradation, and climate change. Problems related to externalization, the tragedy of the commons, and free riders that create market failure must be addressed by smart regulation and institutional change, focusing on the incentive structures leading to ecological degradation and ineffective use of resources. New ideas and concepts focusing on smart regulation, involving stakeholders and people affected by the regulation in the legislative process, as well as stimulating innovation, are needed. Property and market-based solutions, like cap-andtrade systems for the distribution of climate and fishing quotas, also need to be developed in other areas. More substantial effort should be put into finding the most effective solution to the problem each measure is intended to solve.